Navigating the Dynamics: Modeling of Wave Propagation at Taiping Bay Port for Enhanced Design and Management - Dachuan He; Xi Zhang; Yakun Liu; Zhi Chen; Xiangjun Nie; Ke Wang (Journal of Marine Science and Engineering)
This study presents a systematic analysis of wave propagation dynamics at Taiping Bay Port in Dalian, characterized by its deep navigation channel, narrow port entrance, and complex bathymetric features. This study addresses the gap in numerical simulations for extra-large port areas using an integrated modeling approach. Specifically, this research advances our understanding of wave behaviors in harsh maritime environments through an innovative coupling of the parabolic mild slope (PMS) wave model with the phase-resolving Boussinesq wave (BW) model. The PMS model, validated against measured data, effectively computes the incident boundary conditions for the BW model, which in turn has been refined to enhance wave prediction accuracy and model stability through optimized boundary settings. Our findings elucidate the intricate wave patterns and transformations within the harbor, highlighting the significant impact of the deep navigation channel on wave attenuation. This work not only contributes to the theoretical modeling of wave dynamics but also offers practical insights for the design and management of similar complex port structures, potentially guiding future developments in coastal engineering.